2011
DOI: 10.1152/ajpgi.00521.2010
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydrolysate-induced cholecystokinin secretion from enteroendocrine cells is indirectly mediated by the intestinal oligopeptide transporter PepT1

Abstract: Dietary protein is a major stimulant for cholecystokinin (CCK) secretion by the intestinal I cell, however, the mechanism by which protein is detected is unknown. Indirect functional evidence suggests that PepT1 may play a role in CCK-mediated changes in gastric motor function. However, it is unclear whether this oligopeptide transporter directly or indirectly activates the I cell. Using both the CCK-expressing enteroendocrine STC-1 cell and acutely isolated native I cells from CCK-enhanced green fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 45 publications
2
47
0
1
Order By: Relevance
“…We demonstrated that, in response to protein hydrolysates and a tripeptide, STC-1 cells secrete CCK, as has been shown previously (7,21,25,37,48,52,60) (Fig. 1).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We demonstrated that, in response to protein hydrolysates and a tripeptide, STC-1 cells secrete CCK, as has been shown previously (7,21,25,37,48,52,60) (Fig. 1).…”
Section: Discussionsupporting
confidence: 87%
“…Recent work has shown that the peptide transporter PepT1 is not the I cell luminal membrane receptor involved in mediating peptoneinduced CCK release (37), while the GPCR GPR93 has been proposed as a candidate sensor for peptones in STC-1 cells (8). Further work is required to confirm the peptone-sensing role of this GPCR in the intestine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meat hydrolysate has been demonstrated to trigger GLP1 release from vascularly perfused rat small intestine, STC-1 cells (a small intestine enteroendocrine murine cell line) (52), and NCI-H716 cells (derived from human colorectal adenocarcinoma) (53), as well as CCK release from I cells (54). The sensing of these larger protein digestion products has been linked to the activation of MAPKs (52, 53) and the activity of the brush border H + -coupled transporter of dipeptides and tripeptides, peptide transporter 1 (PEPT1) (54,55). Both PEPT1-and CaSR-dependent pathways were recently implicated in the sensing of peptones and dipeptides and tripeptides by primary L cells (56).…”
Section: Molecular Mechanisms Underlying Gut Chemosensingmentioning
confidence: 99%
“…The small peptides are absorption substrates of the intestinal lumen, which can efficiently accelerate the growth of villi, promote the proactive development of the intestinal tract, and elevate intestinal digestive enzyme activity (Bamba, Fuse, Obata, Sasaki, & Hosoda, 1993). Meanwhile, the rapid absorption of small peptides and free amino acids can trigger intracellular calcium-mediated signaling events, followed by the release of more digestive enzymes (Liou et al, 2011). Nevertheless, the intestinal digestive enzyme activity showed no significant increase with increasing replacement proportions (FMBH48, FMBH64, or FMBH80).…”
Section: Discussionmentioning
confidence: 99%